Feasibility Study of Performance Low Capacity Hybrid Energy Power Plant System in Remote Area - Samsurizal, Samsurizal; Azis, Hastuti; Azzahra, Septiannissa; Martiningsih, Wahyuni (Politeknik Negeri Semarang, 2022)
The fossil energy utilization for electricitygeneration is currently starting to be limited because it is predictedthat the availability of fossil energy for the next few decades willrun out. Renewable energy is an alternative energy that can beused to generate electricity. Solar power plant is one of theelectrical energy generators with renewable energy sources thathave been widely used. Solar power plant is a DistributedGenerator that can be applied directly to consumers and it is verysuitable for use in remote areas which currently still use diesel asa fuel for power generation. In this research, the design of a hybridpower generation system between Soalr Energy and Wind will becarried out to replace the use of diesel as a source of electricitygeneration. After the generator design is done, then theperformance test of the hybrid system will be carried out in orderto see the feasibility of the design that has been made. From thetest results, the results of the Hybrid Energy Generator haveefficiencies ranging from 10-12% where this shows that the powerplant system is still said to be unable to work efficiently. Theaverage amount of energy produced from this Hybrid PLT systemis 1,304 kWh per day. Based on the results of the economicfeasibility analysis, that the use of the hybrid system is able toproduce savings of Rp. 1,700 ”“ Rp. 2,100/kWh per day